The phytochemical investigation and biological activity of Nepeta clarkei - Najeeb Rehman; Hidayat Hussain; Nusrat Bakht; Liaqat Ali; Abdul Latif Khan; Ahmed Al-Harrasi; Javid Hussain (International Journal of Phytomedicine, 2016)
The present study is aimed at the isolation and identification of the compounds responsible for the bioactive behavior of Nepeta clarkei (Hook. f). The crude extract and its various sub-fractions obtained from N. clarkei Hook. f. (chloroform (NCC), n-hexane (NCH), ethyl acetate (NCE), and aqueous (NCW)) along with methanolic extract were screened for anti-cancer activity. Only NCH and NCC fractions suppressed the cancer cell lines (HT29 and HCT116) to less than 20% and were screened for a range of other biological activities (antiglycation, phytotoxicity, antiplattelt, insecticidal and antimicrobial) in vitro. The chloroform fraction exhibited significant (63.31%) antiglycation activity followed by the n-hexane fraction (43.9%). Interestingly n-hexane fraction demonstrated a significant phytotoxic potential (100% inhibition) towards Lemna minor at the highest concentration (1000 µg/mL) only, while the chloroform fraction showed moderate activity (33.83%). The n-hexane fraction furthermore demonstrated 100% anti-platelet activity against AA (48 µg/mL) and PAF (15 µg/mL). On the other hand both the chloroform and n-hexane fractions were inactive against fungi and bacteria used in the anti-bacterial and anti-fungal assays. The order of toxicity towards brine shrimps was n-hexane > chloroform fractions. An intensive phytochemical investigation of the chloroform extract of N. clarkei resulted in the isolation of nine metabolites including 1,2-benzenedicarboxylic acid bis (2-ethylhexyl) diester (1), eupatorin (2), achillin (3), neoponcirin (4), parvifloroside B (5), decipinol ester A (6), betulinic acid (7), b-sitosterol (8), and β-sitosterol glucopyranoside (9). The structure elucidation was carried out on the basis of 1D (1H- and 13C) and 2D (H-C correlations; HMBC, HSQC) NMR techniques and confirmed by comparison of their physical and spectroscopic data with those reported in literature. All these compounds, to the best of our knowledge, were isolated from N. clarkei for the first time.